2019
DOI: 10.1093/jnci/djz010
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Adjuvant Systemic Regimens on Contralateral Breast Cancer Risk and Receptor Subtype

Abstract: Background An increasing number of breast cancer (BC) survivors are at risk of developing contralateral breast cancer (CBC). We aimed to investigate the influence of various adjuvant systemic regimens on, subtype-specific, risk of CBC. Methods This population-based cohort study included female patients diagnosed with first invasive BC between 2003 and 2010; follow-up was complete until 2016. Clinico-pathological data were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 45 publications
5
46
3
Order By: Relevance
“…The slightly higher invasive CBC risk in DCIS patients compared with all invasive BC patients may be explained by the risk-reducing effect of adjuvant systemic therapy among invasive BC patients 6 , 20 , 21 . In our previous study using NCR data 6 we showed that adjuvant endocrine therapy, chemotherapy, and trastuzumab combined with chemotherapy were associated with overall 54%, 30%, and 43% risk reductions of CBC, respectively. In our study, a large group (57%) of patients with invasive BC received (neo)adjuvant systemic therapy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The slightly higher invasive CBC risk in DCIS patients compared with all invasive BC patients may be explained by the risk-reducing effect of adjuvant systemic therapy among invasive BC patients 6 , 20 , 21 . In our previous study using NCR data 6 we showed that adjuvant endocrine therapy, chemotherapy, and trastuzumab combined with chemotherapy were associated with overall 54%, 30%, and 43% risk reductions of CBC, respectively. In our study, a large group (57%) of patients with invasive BC received (neo)adjuvant systemic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by underlying etiological factors and/or be related to the use of adjuvant systemic therapy among invasive BC patients. Studies have shown that adjuvant systemic therapy influences subtype-specific CBC risk, e.g., endocrine therapy strongly reduces the risk of developing ER-positive CBC, but not ER-negative CBC 6 , 21 . This is supported by our subgroup analyses in patients with stage I BC not receiving adjuvant systemic therapy, who tended to develop similar CBC subtypes compared with DCIS patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations